2016
DOI: 10.1371/journal.pone.0152545
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA Responses between ‘High’ and ‘Low’ Responders to a 16-Wk Diet and Exercise Weight Loss Intervention

Abstract: BackgroundInteractions between diet, physical activity and genetic predisposition contribute to variable body mass changes observed in response to weight loss interventions. Circulating microRNAs (c-miRNAs) may act as ‘biomarkers’ that are associated with the rate of change in weight loss, and/or play a role in regulating the biological variation, in response to energy restriction.ObjectiveTo quantify targeted c-miRNAs with putative roles in energy metabolism and exercise adaptations following a 16 wk diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 32 publications
2
92
0
Order By: Relevance
“…Because microRNAs capture both underlying genetic risk and responses to behavioral factors (e.g. diet and physical activity) they represent several potential biomarker applications. First, as prognostic biomarkers, there is the possibility for improved granularity in detecting glycaemic progression prior to the onset of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Because microRNAs capture both underlying genetic risk and responses to behavioral factors (e.g. diet and physical activity) they represent several potential biomarker applications. First, as prognostic biomarkers, there is the possibility for improved granularity in detecting glycaemic progression prior to the onset of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compelling evidence suggests that circulating miRNAs are associated with obesity . In this context, a set of 26 miRNAs that were mostly described as associated with obesity in a recently systematic review study were found differently expressed in subjects with obesity compared to non‐obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs with potential physiological functions are deregulated in obesity. Accordingly, weight‐reduction strategies induced with a low‐fat diet in mice and surgical procedures or an energy‐restricted diet plus exercise in humans modulate both circulating and adipose tissue miRNA expression. In our study, we failed to found major changes in miRNAs expression in response to the three different dietary interventions in the context of a weight‐loss program, supporting that not all physiological effects necessarily have epigenetic mechanisms (through miRNA changes).…”
Section: Discussionmentioning
confidence: 99%